Herstory : Exploring the Material Life of Gundrada de Warenne - Dempsey, Karen (2021)
Women’s networks – their relations with other women, men, objects and place – were a source of power in various European and neighbouring regions throughout the Middle Ages. This interdisciplinary volume considers how women’s networks, and particularly women’s direct and indirect relationships to other women, constituted and shaped power from roughly 300 to 1700 AD. The essays in this collection juxtapose scholarship from the fields of archaeology, art history, literature, history and religious studies, drawing on a wide variety of source types. Their aim is to highlight not only the importance of networks in understanding medieval women’s power but also the different ways these networks are represented in medieval sources and can be approached today. This volume reveals how women’s networks were widespread and instrumental in shaping political, familial and spiritual legacies.